2006
DOI: 10.1590/s0103-90162006000200006
|View full text |Cite
|
Sign up to set email alerts
|

Yield and fruit quality of industrial tomato under saline irrigation

Abstract: Industrial tomato is the most important vegetable crop of the Brazilian agribusiness. Few researches have evaluated the tolerance of this crop to saline stress. In this study, the effects of five levels of salinity of the irrigation water (1, 2, 3, 4, and 5 dS m-1) and two equivalent proportions of Na:Ca:Mg (1:1:0.5 and 7:1:0.5) were tested on yield and quality of fruits of industrial tomato, cultivar IPA 6. Seedlings were transplanted in rhizotrons and grown under plastic covering until fruit ripening. Volume… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0
7

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(36 citation statements)
references
References 22 publications
2
27
0
7
Order By: Relevance
“…Studies indicate that pH is a key factor in tomato selection [36]. It is suggested that appropriate pH value for industrial tomato should be between 4.18 and 4.4 [32]. The results of this study showed clearly that four out of the six varietiesTropimech, Tatiana, Techiman and Rodade -had pH values above 4.5 and thus may not be suitable for industrial purposes.Two of the varieties, Pawa and Pectofade with pH values of 4.2 and 4.4, respectively fall within the FAO/WHO requirement for desired tomato varieties of pH below 4.5 [32].…”
Section: Titratable Acidity and Ph Of The Juicementioning
confidence: 73%
See 2 more Smart Citations
“…Studies indicate that pH is a key factor in tomato selection [36]. It is suggested that appropriate pH value for industrial tomato should be between 4.18 and 4.4 [32]. The results of this study showed clearly that four out of the six varietiesTropimech, Tatiana, Techiman and Rodade -had pH values above 4.5 and thus may not be suitable for industrial purposes.Two of the varieties, Pawa and Pectofade with pH values of 4.2 and 4.4, respectively fall within the FAO/WHO requirement for desired tomato varieties of pH below 4.5 [32].…”
Section: Titratable Acidity and Ph Of The Juicementioning
confidence: 73%
“…It is suggested that appropriate pH value for industrial tomato should be between 4.18 and 4.4 [32]. The results of this study showed clearly that four out of the six varietiesTropimech, Tatiana, Techiman and Rodade -had pH values above 4.5 and thus may not be suitable for industrial purposes.Two of the varieties, Pawa and Pectofade with pH values of 4.2 and 4.4, respectively fall within the FAO/WHO requirement for desired tomato varieties of pH below 4.5 [32]. Although farmers could cultivate the other varieties for home consumption, they have to switch to these two suitable varieties if they want to produce for industrial purposes.…”
Section: Titratable Acidity and Ph Of The Juicementioning
confidence: 74%
See 1 more Smart Citation
“…Other finding on tomato yield under salinity indicated that unitary increase of water salinity above 1 dS m-1 reduced the commercial and total yield by 11.9 and 11.0%, respectively, and increased the concentration of soluble solids and the titratable acidity of the fruits by 13.9 and 9.4%, respectively [17]. The authors also indicated that total yield, marketable yield, number of marketable fruits and pulp yield reduced with increase in proportion of sodium.…”
Section: Effect Of Water Quality On Tomato Yieldmentioning
confidence: 90%
“…Cuartero and Fernandez-Munoz (1999) recorded a decrease of tomato fruit weight and number when irrigated with water which EC is equal to 2.5 dS m -1 . Campos et al, (2006) compared the effects of five water salinity levels (1, 2, 3, 4, and 5 dS m -1 ) on industrial tomato yield. They concluded that total yield was reduced by 11% upon each unit increase of water salinity while fruit quality improved with increasing water salinity.…”
Section: Crop Yieldmentioning
confidence: 99%